Ethnobotanical Analysis of Mangroves as Food Resources in East Lampung - Mustika Wati, Devi; Duryat, Duryat; Riniarti, Melya (Jurnal Wasian, 2024)
The world is experiencing a food crisis due to climate change, and mangroves as a blue ecosystem have a significant potential to mitigate this crisis. This research seeks to record the ethnobotanical practices of utilising mangroves, as a food source in East Lampung. We employed the snowball sampling method in Margasari village, Purwerejo village, and Karya Makmur village. In addition, we gathered data on mangrove species, parts of used, processing methods, products, and their properties, through interviews and observations. Also, we analysed the data using descriptive analysis to provide a comprehensive overview of the varieties of mangroves, their processing, and the resulting products. This research revealed that the communities employs five distinct varieties of mangroves as sustenance sources. Mangroves produce various food products from their four components: fruit, juvenile leaves, old leaves, and propagules. Notably, processed products, including pidada fruit (Sonneratia caseolaris), are anti-hypertensive, canker sores, and heartburn treatments. Jeruju leaves (Acanthus ilicifolius) are known to improve stamina, and seeds without the root of Rhizophora mucronata propagules act as anti-gastritis agents, improve blood circulation, and prevent anaemia. Although there are ten processed mangrove products, they are still considered traditional and are not as popular among the newer generation.